THE INFLUENCE OF COMPANY CHARACTERISTICS ON COMPANY VALUE(STUDY ON COMPANIES WITH LQ45 STOCK INDEX IN 2021-2023) - Nabila Fitrotus Dzakiya (Adisam Publisher, 2025)
This study aims to see the effect of company characteristics on company value. The variables analyzed include company size, company age, dividend policy, liquidity, and profitability. The data used in this study are secondary data taken directly from the annual report of LQ45 Companies for 2021-2023 listed on the Indonesia Stock Exchange (IDX). The analysis was carried out using an explanatory quantitative approach. The results of the study indicate that the variables of company size, company age, dividend policy, and profitability have a negative effect on company value. On the other hand, the liquidity variable has been shown to have a positive effect on company value.